2010
DOI: 10.1086/650722
|View full text |Cite
|
Sign up to set email alerts
|

The Ontogeny of Plant Defense and Herbivory: Characterizing General Patterns Using Meta‐Analysis

Abstract: Defense against herbivores often changes dramatically as plants develop. Hypotheses based on allocation theory and herbivore selection patterns predict that defense should increase or decrease, respectively, across ontogeny, and previous research partly supports both predictions. Thus, it remains unclear which pattern is more common and what factors contribute to variability among studies. We conducted a meta-analysis of 116 published studies reporting ontogenetic patterns in plant defense traits and herbivory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
475
10
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(526 citation statements)
references
References 49 publications
32
475
10
2
Order By: Relevance
“…Surprisingly few studies have followed ontogenetic trajectories of plant defense expression across multiple years. A recent meta-analysis found increasing investment in defensive chemistry across ontogenetic development for herbaceous plants, but this pattern was restricted to short term developmental changes, typically across the first year of growth (Barton and Koricheva 2010). A few other studies have followed insect attack on a cohort of plants across several years, but in these cases, the impact of changing plant phenotypes was unclear (e.g., Roininen et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly few studies have followed ontogenetic trajectories of plant defense expression across multiple years. A recent meta-analysis found increasing investment in defensive chemistry across ontogenetic development for herbaceous plants, but this pattern was restricted to short term developmental changes, typically across the first year of growth (Barton and Koricheva 2010). A few other studies have followed insect attack on a cohort of plants across several years, but in these cases, the impact of changing plant phenotypes was unclear (e.g., Roininen et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…their ability to enhance the sink strength at the feeding site and out compete other plant sinks for resources; Larson and Whitham, 1997;Wool, 2004). While investigators have acknowledged different responses in defense chemistry and downstream effects on herbivores as plants enter their reproductive stage (Bazzaz et al, 1987;Zangerl and Bazzaz, 1992;Baldwin, 1998;Barton and Koricheva, 2010), there are no clear generalizations regarding the relationship between other naturally occurring competing sinks (young leaves and roots) and plant defense responses. Moreover, recent attempts to develop a conceptual model of changes made to plant resource allocation following herbivore attack that takes into account vascular architecture, tissue development, variation over time, and local environmental variation have been impeded by differences in temporal and spatial variation in responses and by the dependency of induction of local defense responses on other plant modules (Hanhimäki and Senn, 1992;Orians and Jones, 2001).…”
mentioning
confidence: 99%
“…For example, seedlings are much less tolerant of partial consumption [48], and are predicted to err on the side of more defense, similar to animals. Indeed, a meta-analysis found that chemical defenses for woody plants increased during the seedling stage and decreased at later stages [49]. Similarly plants invest heavily in constitutive defense in tissues of high reproductive value (e.g., seeds) but have inducible defenses in leaves and roots, presumably reflecting the high cost of leaving valuable tissues undefended [50].…”
Section: Constraints On Responses To Risk Error Management Strategiesmentioning
confidence: 99%